Contextual Factors of Men's Online Extramarital Relationships: A Qualitative Study - Hajizadeh , Zeinab; Lotfi Kashani, Farah; Vaziri , Shahram; Ahi, Qasem (Journal of Assessment and Research in Applied Counseling (JARAC), 2024)
Objective: Online extramarital relationships, like their real-world counterparts, may lead to marital disputes, separation, and even divorce. Accordingly, this research aims to qualitatively analyze men's online extramarital relationships.Methods and Materials: This study was conducted qualitatively using content analysis methodology. Based on the criterion of theoretical saturation, twelve men participated in this study. Semi-structured interviews were used for data collection. MAXQDA software was utilized for coding and classifying the data.Findings: The factors contributing to the formation of men's online extramarital relationships can be categorized into 14 main categories and 30 subcategories. The factors contributing to the formation of men's online extramarital relationships can be discussed in four domains: individual-personality, familial, cultural-social, and religious beliefs and convictions.Conclusion: The extramarital relationship is a harmful phenomenon that occurs following a chain of individual-personality, familial, cultural-social factors, and religious beliefs and convictions. Given the nature of these factors, planning for prevention, focusing on, and providing necessary training to couples in this area can play a decisive role in reducing online extramarital relationships.